The food system and its interaction with human health and nutrition - Pinstrup-Andersen, Per (International Food Policy Research Institute, 2011)
The food system begins and ends with health and nutrition. Advances in the health sciences, including genomics and stem cell biology, continue to reinforce the principle that nutritious food is essential for the achievement of full physical and cognitive potential for all individuals and populations and for sustaining health through the aging process. Likewise, advances in the social and behavioral sciences are revealing the many dimensions of health, the behaviors that promote health, and the value of health in generating productive agricultural systems and sustainable development. Health is now considered a primary goal and quantifiable endpoint of food systems. It is also an emerging force in agricultural policy, driven in part by the emergence of the “triple burden” of malnutrition—the coexistence of hunger, nutrient deficiencies, and excess intake of calories leading to overweight and obesity in many poor countries—that has resulted in part from a lack of harmony between food systems and the promotion of human health.